Managerial Ability, Corporate Social Responsibility, Tone of Earnings Announcement and Market Reaction in Indonesia - Lies Indit Faidah; Bandi Bandi (Jurnal Ilmiah Akuntansi, 2022)
This study aims to provide empirical evidence and discuss the effect of earnings announcement tone on market reaction with managerial ability and corporate social responsibility as moderating variables. The market reaction was proxied by cumulative abnormal return (-2.04). This study used a sample of 924 companies that were included in the Indonesia Sharia Stock Index (ISSI) from 2014 to 2019 was carried out by the purposive sampling method. Multiple linear regression analysis was used to test the first hypothesis and moderated regression analysis was used to test the second and third hypotheses. The results showed that tone of earnings announcement had a positive effect on market reaction, managerial ability moderate or strengthen the relationship between earnings announcement tone and market reaction, and CSR did not moderate the relationship between earnings announcement tone and market reaction. The results of the study of control varibel showed that size had a positive effect on market reactions and ROA had no effect on market reactions